A mixed Cd/Cu-based metal-organic framework achieved by postsynthetic metal exchange for electrocatalytic oxidation of uric acid - Ma, Yun-Xiang (2023)
In this work, we designed a Cd/macrocycle-based metal-organic framework (MOF), namely, [Cd5O(L)(H2O)4]4DMF·5H2O (Cd-L) (L8-= calix[4]resorcinarene-based carboxylate ion and DMF = N,N-dimethylforamide). The pentanuclear Cd-O clusters are linked by L8-anions to form a polymeric structure. Eight coordinated Cd(II) ions in Cd-L can be replaced by Cu(II) ions through a postsynthetic metal exchange method in an aqueous solution at room temperature to afford a CdCu bimetallic MOF [Cd4OCu(L)(H2O)4]DMF·7H2O (CdCu-L). Electrochemical analysis shows that the conductivity of CdCu-L increases by about 3 times after the introduction of copper ions into Cd-L. On account of the unique structure, CdCu-L is used for electrocatalytic detection of uric acid (UA) in real samples. For UA with various concentrations from 10 to 500 μM, the oxidation peak current of the CdCu-L-based electrode increases linearly, and the detection limit of UA is calculated to be 2.67 μM. The CdCu-L-based electrode exhibits high selectivity, reproducibility, and stability during the UA detection. This research presents a mixed Cd/Cu-based MOF for efficient electrocatalytic oxidation of UA.